2018
DOI: 10.1111/evj.12830
|View full text |Cite
|
Sign up to set email alerts
|

Salpingopharyngeal fistula as a treatment for guttural pouch mycosis in seven horses

Abstract: Salpingopharyngostomy can minimise cost of treatment, be performed on an outpatient basis and provide better exposure of the infected area with few complications. This case series documents seven cases treated with this method that resolved the infection without any further complications of the mycosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 33 publications
1
30
0
Order By: Relevance
“…How much the size of the fenestrations will decrease with healing or whether a predictable patency can be achieved is unknown. Previous work has shown that while some fenestration sites heal, others remain patent on follow-up [ 6 7 19 ]. One study hypothesized that fenestration within the guttural pouch can alter the local environment triggering the resolution of mycosis [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…How much the size of the fenestrations will decrease with healing or whether a predictable patency can be achieved is unknown. Previous work has shown that while some fenestration sites heal, others remain patent on follow-up [ 6 7 19 ]. One study hypothesized that fenestration within the guttural pouch can alter the local environment triggering the resolution of mycosis [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that while some fenestration sites heal, others remain patent on follow-up [ 6 7 19 ]. One study hypothesized that fenestration within the guttural pouch can alter the local environment triggering the resolution of mycosis [ 19 ]. Despite these questions, it is apparent that diverticulotomy is therapeutic when applied to selected primary diseases of the guttural pouch, including tympany, empyema, and chondroids [ 7 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This retrospective clinical report by Amanda Watkins and Eric Parente , based at the University of Pennsylvania in the USA, describes the use and outcome of transendoscopic laser salpingopharyngostomy for treatment of guttural pouch mycosis (GPM) in horses .…”
Section: Guttural Pouch Mycosismentioning
confidence: 99%